Analisis Komposisi Adelita Karya Francisco Tarrega - Adi Marianto; Esy Maestro (FBS Universitas Negeri Padang, 2021)
This study aims to describe the results of an analysis of Adelita's music composition in terms of melody, rhythm, and harmony analyzed based on motives, themes, phrases, and periods. It aims to find out the creation concept made by the composer. This research belongs to a qualitative descriptive analysis research. The main instrument in this study was the researcher itself. The researcher processed the data by doing some steps such as reading scores from Adelita's material, then classifying the data from understanding music theory, from the structural aspect, as well as the melody, rhythm, and harmony, so that the researcher can make a summary of the data found in the form of writings which describe an understanding of music theory. Then, the researcher conducted a feasibility test on the song with the aim that the song analyzed can be used as a learning material for students studying classical guitar material and as an eligibility to be taken as musical knowledge. The results show that Adelita's work is unique in terms of playing techniques and ornamentation. By using simple melody, rhythm, and harmony, Adelita can be accepted as a reference for learning classical guitar. The assessment was obtained from simple melody, rhythm, and harmony analysis. Thus, it can be used as a reference for learning classical guitar for students who take the course of classical guitar major instrument.